Retrospective study of calf mortality on central cattle breeding and dairy farm (ccbdf) in bangladesh - Md. Mukter Hossain; Abu Hena Mustafa Kamal; AKM Anisur Rahman (Eurasian Journal of Veterinary Sciences)
Aim: The objective of this study was to find out the underlying causes and factors which are associated with calf mortality. Materials and Methods: The 16 (1992-2007) year's data of calf mortality in the Central Cattle Breeding and Dairy Farm (CCBDF) were analyzed for season, age, sex, breed and etiology. Results: Female calves (56.77%) died more than males (43.23%). The mortality was significantly higher in exotic and crossbred animals than in local/indigenous calves. Mortality rate were 28.99%, 33.03% and 37.98% in rainy, summer and winter season, respectively. The major causes of death were respiratory tract disease (38.75%), tuberculosis (20.02%) and alimentary tract infections (16.73%). The other causes of death in calves occurred in the following frequencies: Malnutrition (5.28%), debility (4.72%), hairball (3.12%), babesiosis (2.56%), internal haemorrhage (2.56%), tympanitis (2.24%), black quarter (2.24%) and foot and mouth disease (1.76%). Age is the most important factor and significantly associated with mortality. Conclusion: Calves of first month of life may have higher mortality risk.